The Influence of Microstructure on Sound Absorption of Polyurethane Foams through Numerical Simulation. Issue 5 (5th April 2021) - Chen, Shuming; Lei, Shuai; Zhu, Junhao; Zhang, Tao
Abstract: It exists an unchanging requirement in modern society to achieve an ideal fuel economy using light acoustic packaging with good sound absorption performance. The Polyurethane (PU) foam with excellent damping properties usually has the characteristics of low mass and low density. Therefore, it is often considered as an ideal sound‐absorbing packaging material. With the further research on the PU foam, we have learned that the inherent microstructure of the PU foam has a special effect on its sound absorption performance. In this paper, the authors theoretically demonstrate the effect of cell size, connectivity and relative pore diameter on sound absorption performance by numerical simulation analysis. From the numerical simulation analysis, the results show that the three cellular structure factors have different effects on the parameters of the Johnson‐Champoux‐Allard (JCA) acoustic model, and all of them can improve the sound absorption coefficient of PU foam. Additionally, the further analysis indicates that the relative pore diameter is the most vital factor to improve the sound absorption performance in the entire frequency domain. This research could be applied to industrial production to reduce the amount of acoustic packaging material used in vehicles while improving the acoustic quality of vehicles. Abstract : Soybean oil‐based polyol replaces part of petroleum polyol to prepare polyurethane foam. The foam microstructure is replicated to create periodic unit cell models. The theoretical sound absorption coefficients of different models are obtained by using Johnson‐Champoux‐Allard acoustic model. The effects of cell size, relative pore diameter,  and connectivity on sound absorption performance are studied through experiments and simulations.